Impact of Atomic Layer-Deposited Hydroxyapatite-Coated Titanium on Expression of Focal Adhesion Molecules of Human Gingival Fibroblasts - Nagat Areid; Faleh Abushahba; Sini Riivari; Elisa Närvä; Elina Kylmäoja; Mikko Ritala; Juha Tuukkanen; Pekka K. Vallittu; Timo O. Närhi (Nanomaterials)
This study investigated the impact of the nanocrystalline atomic layer-deposited hydroxyapatite (ALD-HA) coating of titanium (Ti) surface on the attachment and proliferation of human gingival fibroblasts (HGFs). Ti discs were divided into ALD-HA-coated and non-coated (NC) controls. HGFs were harvested from gingival biopsies of patients subjected to extraction of their third molar. The cells were cultivated on the Ti discs for 2 and 24 h to evaluate the initial cell attachment using confocal microscopy. Spreading of cells and the signals of focal adhesion proteins were measured. Moreover, the adhesion proteins vinculin and paxillin expression levels were evaluated using Western blot after 3 d of cultivation. In addition, the proliferation of HGF was assessed by cultivating the cells on Ti discs for 1, 3, and 7 d. Fibroblast spreading was significantly greater on ALD-HA surfaces than on NC surfaces after 2 h (p < 0.001). In addition, the signals of vinculin and paxillin were significantly higher on the ALD-HA than on the NC surfaces at 2 and 24 h. The confocal microscope analysis also revealed significantly higher expression of focal adhesion molecules on ALD-HA surfaces at both time points. Furthermore, the cell proliferation rate was significantly higher at d 3 (p = 0.022) and d 7 (p < 0.001) on the ALD-HA compared to the NC surfaces. These findings indicate that ALD-HA coating enhances focal adhesion formation, cell spreading, and proliferation on Ti surfaces, suggesting its potential to improve gingival tissue attachment to Ti implant surfaces.